Effect of concurrent zidovudine use on the resistance pathway selected by abacavir-containing regimens. - Lanier, E; Givens, N; Stone, C; Griffin, P; Gibb, D; Walker, S; Tisdale, M; Irlbeck, D; Underwood, M; St Clair, M; Ait-Khaled, M (2004)
OBJECTIVES: Abacavir (ABC) selects for four mutations (K65R, L74V, Y115F and M184V) in HIV-1 reverse transcriptase (RT), both in vitro and during monotherapy in vivo. The aim of this analysis was to compare the selection of these and other nucleoside reverse transcriptase inhibitor (NRTI)-associated mutations by ABC-containing therapies in the presence and absence of concurrent lamivudine (3TC) and/or zidovudine (ZDV) and to assess the effect of these mutations on phenotypic susceptibility to the NRTIs. DESIGN: This study was a retrospective analysis of the patterns of NRTI-associated mutations selected following virological failure in six multicentre trials conducted during the development of ABC. METHODS: Virological failure was defined as confirmed vRNA above 400 HIV-1 RNA copies/mL. RT genotype and phenotype were determined using standard methods. RESULTS: K65R was selected infrequently by ABC-containing regimens in the absence of ZDV (13 of 127 patients), while L74V/I was selected more frequently (51 of 127 patients). Selection of both K65R and L74V/I was significantly reduced by co-administration of ZDV with ABC (one of 86 and two of 86 patients, respectively). Y115F was uncommon in the absence (seven of 127 patients) or presence (four of 86 patients) of ZDV. M184V was the most frequently selected mutation by ABC alone (24 of 70 patients) and by ABC plus 3TC (48 of 70 patients). Thymidine analogue mutations were associated with ZDV use. The K65R mutation conferred the broadest phenotypic cross-resistance of the mutations studied. CONCLUSIONS: The resistance pathway selected upon virological failure of ABC-containing regimens is significantly altered by concurrent ZDV use, but not by concurrent 3TC use. These data may have important implications for the efficacy of subsequent lines of NRTI therapies.